Antigenic relationship between mugwort and ragweed pollens by crossed immunoelectrophoresis. - Park, H. S. (Korean Academy of Medical Sciences, 1994)
Mugwort and ragweed pollens have been considered as important respiratory allergens in Korea. These two pollens are abundant in the air of Seoul from August through October. Many ragweed-sensitive patients have shown concurrent sensitivities to mugwort pollen. However the antigenic relationship between these two pollens has not been clarified. To observe the cross-reactivity between them, we developed polyclonal anti-mugwort and anti-ragweed antibodies by immunization on New Zealand white rabbits, and performed crossed immunoelectrophoresis(CIE) with two pollen extracts. Five precipitation lines were formed by mugwort and anti-mugwort antibody. One precipitation line was formed by ragweed and anti-ragweed antibody. There was no reaction from mugwort and anti-ragweed antibody, and from ragweed and anti-mugwort antibody. These results indicate that there is no cross-antigenicity between mugwort and ragweed pollens.